Implementasi Kebijakan Kawasan Tanpa Rokok (KTR) di Kabupaten Sumbawa - Apriadi, Budi Kurniawan, Topan Rahmatul Iman (Prodi Ilmu Administrasi Negara, 2019)
The magnitude of the impact of smoking on health and the high number of smokers in Indonesia, prompted the government of the Republic of Indonesia to make policies related to this. Sumbawa Regency as one of the regencies in West Nusa Tenggara Province is participating in realizing a non-smoking area by passing regional regulation number 7 of 2016. But smoking activities are still often found in public transportation, children's playground areas, in health and education service facilities in Sumbawa Regency. The purpose of this study is to find out how the implementation of regional regulation number 7 of 2016 on No Smoking Areas (KTR) in Sumbawa Regency. The research method used is a qualitative research method with a descriptive approach, which describes the implementation of the policy of no-smoking area in Sumbawa Regency. The results of this study are the implementation of policies on non-smoking areas in Sumbawa Regency which are not yet running, the Regional Organization of Organizations (OPD) which have a connection in the implementation of these regulations do not understand the mechanism of implementing these regulations so that there are no programs or activities in related agencies that are trying to realize and encourage the creation of a non-smoking area in Sumbawa